2021
DOI: 10.1177/20416695211040237
|View full text |Cite
|
Sign up to set email alerts
|

Perception of the Potential for Interaction in Social Scenes

Abstract: In urban environments, humans often encounter other people that may engage one in interaction. How do humans perceive such invitations to interact at a glance? We briefly presented participants with pictures of actors carrying out one of 11 behaviors (e.g., waving or looking at a phone) at four camera-actor distances. Participants were asked to describe what they might do in such a situation, how they decided, and what stood out most in the photograph. In addition, participants rated how likely they deemed int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 65 publications
1
2
0
Order By: Relevance
“…In fact, one recent study used short (500ms) presentations of potentially social images (e.g., a person waving to the viewer, a person looking away or at their phone) and found that participants were able to see the affordances of these scenes, in that they provided clear and consistent responses to what they would do in such a situation (e.g., speak to person in the image, walk past, gesture). The authors suggest, in line with the current framework, that such social scenes also present a type of Gestalt that provides social affordances (Hessels et al, 2021) which interactions are based on. Note, however, that we are not using the term "social affordance" to indicate a different sort of affordance per se (see, e.g., (Baggs, 2021)), but rather to differentiate social affordances in an interaction from the affordances associated with perceptual objects.…”
Section: Social Affordances and Interactional Embeddingsupporting
confidence: 64%
See 1 more Smart Citation
“…In fact, one recent study used short (500ms) presentations of potentially social images (e.g., a person waving to the viewer, a person looking away or at their phone) and found that participants were able to see the affordances of these scenes, in that they provided clear and consistent responses to what they would do in such a situation (e.g., speak to person in the image, walk past, gesture). The authors suggest, in line with the current framework, that such social scenes also present a type of Gestalt that provides social affordances (Hessels et al, 2021) which interactions are based on. Note, however, that we are not using the term "social affordance" to indicate a different sort of affordance per se (see, e.g., (Baggs, 2021)), but rather to differentiate social affordances in an interaction from the affordances associated with perceptual objects.…”
Section: Social Affordances and Interactional Embeddingsupporting
confidence: 64%
“…The principle of perceiving affordances, which was first discussed in terms of visual affordances such as graspability, can be extended to social affordances. According to this view, social affordances allow us to rapidly determine whether there are other individuals with whom we can interact and what the likely outcomes of such as an interaction may be ( Hessels et al, 2021 ; Valenti & Good, 1991 ; van Dijk & Kiverstein, 2021 ). This does not need to be interaction in the sense of language or communication.…”
Section: Gestalt Perception Within and Across Sensory Modalitiesmentioning
confidence: 99%
“…We employ the same approach for statistical group-comparison as in our previous study (Hessels, Benjamins, van Doorn, Koenderink, & Hooge, 2021 ). That is, we report the Harrell-Davis estimated median and use nonparametric bootstrapping to compute the 95% confidence intervals around the median using the decilespbci MATLAB function provided by Rousselet, Pernet and Wilcox ( 2017 ).…”
Section: Methodsmentioning
confidence: 99%